Variability of the atmospheric ozone over Kathmandu using ground-based measurements - Chapagain, NP (BIBECHANA, 2015)
Measurement of the atmospheric total ozone over Kathmandu (27.67°N, 85.29°E) was carried out with a Brewer Spectrophotometer from February 2001 through February 2002. The total ozone data obtained from Brewer instrument are analyzed to study the daily variations of total ozone over Kathmandu on different seasons. The results reveal that day-to-day variations of the total ozone over Kathmandu are seasonal dependent. Total ozone values are relatively high in summer and spring seasons (up to 327 DU) and low (~213 DU) during the winter season. The low ozone concentration would be due to chemical and dynamic destruction processes related to the low temperature and less active photochemical reaction as less intense solar radiations are received during winter season. BIBECHANA 13 (2016) 9-17